IMAGO DEI AND DESIRE IN GENESIS: 1–3. TO EAT OR NOT TO EAT; OR RATHER TO EAT OR WHAT TO EAT - Andersen, Kirsten M. (Literature and theology, 1992)
Kirsten M. Andersen; IMAGO DEI AND DESIRE IN GENESIS: 1–3. TO EAT OR NOT TO EAT; OR RATHER TO EAT OR WHAT TO EAT, Literature and Theology, Volume 6, Issue 3, 1